A selective microalgae strain for biodiesel production in relation to higher lipid profile - Bhuyar, P.; Mohd Hasbi, Ab. Rahim; M. M., Yusoff; Gaanty Pragas, Maniam; Govindan, Natanamurugaraj (School of Renewable Energy, Maejo University, 2019)
Biodiesel have become the important asset by the country especially to build up their economy. Currently, microalgae have been choosing as the source for production of biodiesel based on their advantages. Microalgae are a photosynthetic organism that use light as an energy source and able to produce their own food. These microalgae also produce a lipid that can be used to produce a biodiesel. Using microalgae that contain high lipid profile are very important to make sure the biodiesel can be produce in large quantity in short time and more cost saving. Although many microalgae species have been identified and isolated for lipid production, there is currently no consensus as to which species provide the highest productivity. Different species are expected to function best at different aquatic, geographical and climatic conditions. So, this experiment is conducted to identify which strain of microalgae contains high lipid profile that can be used to convert into the biodiesel. There are three main objectives that involve in this experiment which is to isolate and identify different strain of microalgae from Kuantan Coast, East Coast Peninsular Malaysia, to convert the lipid from microalgae into biodiesel through transesterification, and to estimate higher lipid profile of microalgae species for biodiesel production. Two species of green microalgae were isolated, which is Nannochloropsis sp and Coelastrum sp. Based on lipid extraction and lipid analysis, it shows that the Nannochloropsis sp. have more concentrated of lipid and higher lipid profile compared to Coelastrum sp. Hence, Nannochloropsis sp. are most suitable species that can be used as a biodiesel feedstock due to higher lipid profile of MUFA.